Perubahan Sosial Budaya Akibat Media Instagram bagi Kalangan Mahasiswi di Kota Padang - Elva Ronaning Roem; Sarmiati Sarmiati (Universitas Andalas, 2019)
Socio-cultural changes in the world of social media always occur because of the support of sophisticated technology that occurs to this day. One of them is the use of Instagram for millennials, including in Padang. This research is to find out how social change is and the impact that occurs on students in Padang in using Instagram. This research was conducted in Padang, using a case study approach by conducting in-depth interviews with 25 students who were active in using Instagram with a daily usage frequency of more than 12 to 24 hours. The results showed that the use of Instagram had an impact on the emergence of social and cultural changes for students in Padang. First, they do not hesitate to share excessively in self-disclosure in cyberspace. This culture certainly arises because of the presence of Instagram as one of the social media that can be accessed by anyone. Second, students are not able to provide boundaries between private space and public space, so Instagram currently also has an influence as a channel or medium in complementing relationships among themselves, and at the same time Instagram is part of the lifestyle chosen by students when communicating using sophisticated technology.